Production of alkaloid Capsaicine of chili Pepper and Callus initiated from them - Mzahim Al Mallah; Ghada Al-Youzbaki (College of Education for Pure Sciences, 2005)
Capsnicine was obtained from tlie alcoholic extracts of different explains of the chili pepper seedlings, callus and fruits. Dragendorff test was conducted to identify the isolated alkaloid which showed positive reaction. The isolated alkaloid was idem i [led depending on the diagnosticmethods including measurement of ah-orbanee values (A max) by UV Spectrophotometer, Thin layer chromatograpical technique demonstrated the separation of one spot from each tested sample having the same value of rate How which coincided with the rate flow value of the control. All samples were then identified by determining its chemical structure using NMR. This test showed similarity between the chemical structures of the isolated alkaloid with the structure of standard capsaicine. The results of the quantitative determination proved differences of capsaicine in explants and caili. Fruits were in first order of containing this alkaloid followed by stems, leaves, leaf petiole and shoot tips. The stimulated callus was identical in its alkaloid content with that of the explant, from which was initiated,